Development of a tool for managing groundwater resources in semi-arid hard rock regions: application to a rural watershed in South India - Dewandel, B.; Perrin, J.; Ahmed, S.; Aulong, S.; Hrkal, Z.; Lachassagne, P.; Samad, Madar; Massuel, S. (Wiley, 2010)
Until recently, aquifers located in hard rock formations (granite, gneiss, schist) were considered as a highly heterogeneous media, and no adequate methodology for groundwater management was available. Recent research studies have shown that when hard rocks are exposed to regional and deep-weathering processes and when the geology is relatively homogenous, a typical hard rock aquifer is made of two main superimposed hydrogeological layers each characterized by quite homogeneous specific hydrodynamic properties: namely the saprolite and the fissured layers. Therefore, for these cases, hard rock aquifers can be considered as a multi-layered system. Based on these works, an operational decision support tool (DST-GW ) designed for the management of groundwater resources in hard rock area under variable agro-climatic conditions has been developed. The tool focuses on the impact of changing cropping pattern, artificial recharge and rainfall conditions on groundwater levels at the scale of small watersheds (10 to about 100 km2 in case well-developed weathering profile). DST-GW is based on the groundwater balance and the 'water table fluctuation method', which are well-adapted methods in hard rock and semiarid contexts. Based on field data from an overexploited South Indian watershed (58 km2), the model allows calibrating, at watershed scale, the variation in specific yield of the aquifer with depth, as well as the rainfall-aquifer recharge relationship. Seasonal basin-scale piezometric levels are computed with an average deviation of ?0?56 m compared to measurements from 2001 to 2005. The model shows that, if no measure is taken, the water table depletion will induce the drying-up of most of the exploited borewells by the year 2012. Scenarios of mitigation measures elaborated with the tool show that change in cropping patterns could rapidly reverse the tendency and lead to a sustainable management of the resource. This work presents the developed tool and particularly the hydraulic model involved in and its application to a case study. However, the purpose tool is applicable at watershed scale but not design for the groundwater management of a very small area or for a single borewell.